Effects of Melatonin Hormone on Oxytocin-Induced Myometrium Contractions in Rats - Pekmez, Hıdır; Kuş, İlter; Ögetürk, Murat; Kutlu, Selim; Zararsız, İsmail; Sarsılmaz, Mustafa (Fırat University, 2004)
Objective: The aim of this study was to investigate the effects of melatonin, a hormone, on oxytocin-induced contractility of isolated myometrium. Materials and method: Myometrial strips were removed from a total of 25 non-pregnant Wistar female rats (weighing 200-250 g), which were confirmed to have regular sexual cycle by vaginal smear technique. Animals in oestrus cycle were sacrificed by decapitation and isolated uterus placed in a petri dish containing the Krebs solution. About 1X0.2X0.1 cm myometrium strips were isolated and placed in an organ bath containing Krebs solution at 37 degrees C and pH 7.4, constantly bubbled with 95% oxygen - 5% carbon dioxide. Isometric contractions were recorded under 1 gram of resting tension. After a 30-120 minutes equilibration period myometrial strips were stimulated with oxytocin and the effects of different doses of melatonin (1mM, 3mM, 5mM) were applied. Results: Oxytocin-induced contractions of myometrium were accepted as control. 1mM dose of melatonin hormone reduced these contractions particularly, whereas administration of 3mM melatonin showed a moderate inhibitor effect. However, administration of 5mM dose of melatonin was seen to completely inhibit the oxytocin-induced myometrial contractions.Conclusion: It was determined that melatonin had an inhibitory effect on the contractions of myometrium.

Amaç: Bu çalışma, oksitosin ile indüklenen izole miyometriyum kasılmaları üzerine melatonin hormonunun etkilerinin araştırılması amacıyla yapıldı.Gereç ve yöntem: Vajinal simir ile düzenli siklus gösterdiği tespit edilen 200-250 gram ağırlığındaki gebe olmayan 25 adet yetişkin Wistar cinsi dişi sıçanlar kullanıldı. Östrus evresindeki sıçanlar dekapite edildikten sonra, uterus çıkarılıp içerisinde Krebs solusyonu bulunan petri kutusuna alındı. 1X0.2X0.1 cm. boyutlarında miyometriyum kesitleri hazırlandıktan sonra, içerisinde %95 oksijen ve %5 karbondioksitle sürekli gazlandırılan PH 7,4 ve 37oC'de Krebs solüsyonu bulunan organ banyosuna alındı. Miyometriyal kesitler 1 gramlık istirahat gerimi altında asılarak kontraksiyonlar kayıt edildi. Miyometriyum kesitlerinde 30 dakika ile 2 saat arasında spontan kasılmalar gözlendi. Bu kasılmalar bittikten sonra miyometriyum aktivitesi oksitosin uygulanarak anlamlı bir şekilde artırıldı. Daha sonra melatoninin farklı dozları (1mM, 3mM, 5mM) uygulandı. Bulgular:Oksitosin ile indüklenmiş miyometriyum kontraksiyonları kontrol olarak kabul edildi. 1mM dozundaki melatonin hormonunun bu kontraksiyonları kısmen azalttığı, 3mM melatonin uygulamasının da orta derecede bir inhibitör etki gösterdiği belirlendi. 5mM dozda uygulanan melatoninin ise oksitosinle indüklenmiş miyometriyum kontraksiyonlarını tamamen inhibe ettiği görüldü.Sonuç: Melatonin hormonunun miyometriyum kontraksiyonları üzerinde inhibitör bir etkiye sahip olduğu tespit edildi.
Sıçanlarda Oksitosinle İndüklenmiş Miyometriyum Kasılmaları Üzerine Melatonin Hormonunun Etkisi